Fear Of Missing Out (FOMO) Pada Remaja Pengguna Media Sosial: Studi Pendahuluan - Nurul Fazria; Firman; Netrawati (CV. ITTC INDONESIA, 2024)
Fear of missing out (FoMO) is a psychological phenomenon that arises when someone feels anxious or worried about missing out on information or experiences that others have, especially those shared through social media. The population in this study were adolescent social media users in Padang City. This research is a preliminary study using descriptive quantitative to reveal the description of fear of missing out (FoMO) in adolescent social media users. The data collection technique was carried out through the ONFoMO scale which was distributed via google forms and selected using purposive sampling technique. Samples that fit the specified criteria were 272 samples. The results showed that most respondents were aged 17-21 years (84%) with the majority of female gender (60%). The duration of social media use is mostly in the range of 1-5 hours per day (70%) with WhatsApp as the social media that is entirely owned by teenagers. The results showed that almost half of the adolescents (35.7%) were at a high level of FoMO with aspects such as anxiety, the need to be accepted and popular, and social media addiction playing a significant role in influencing fear of missing out (FoMO). This study shows that the phenomenon of high FoMO among adolescents is related to patterns of intensive social media use. This study is expected to provide an overview for related parties in designing interventions to manage social media use among adolescents.